Bem-estar no ambiente de trabalho sob o ponto de vista da Psicologia positiva - Closel, Ursula de Oliveira (2017)
The present dissertation had as objective to study the elements that can interfere in the well-being of the servers, in the working environment of a Federal Educational Institution, from the accomplishment of a qualitative descriptive and bibliographical research. In broader terms, the phenomenological method permeated all work. The data were collected through non-participatory observation at the site, to identify the subjects of the research, who may be offered an interview participation, in semistructured format. The material collected from the observations and transcripts of the interviews were analyzed considering a phenomenological perspective and the constructions of Positive Psychology, also using content analysis. The results were found that, for the interviewed employees, the well-being in the work environment is related to the development of healthy relationships, recognition and appreciation instead, concern, concern and zeal with the other, in addition to living with positive and satisfied. The lack of respect and empathy, inappropriate behaviors and postures of employees, gossip, criticism, lack of dialogue and reciprocity. It was also possible to perceive that the welfare experience is predominantly related to the presence of favorable conditions for the individual to develop his abilities and talents and the institution of his contribution in the process. Finally, it was suggested actions that can help promote the working environment, an interaction between the servers and their well-being.